The Role of Brand Awareness Mediating the Influence of Social Media Marketing on Purchase Intention - I Gusti Bagus Krisna Saputra; I Made Wardana (International Journal of Asian Business and Management, 2023)
Social media marketing can be utilized as a digital marketing channel to establish brand awareness, as a well-known brand provides a sense of security and makes it easier for potential customers to identify a brand. Strong brand awareness has a greater chance of being chosen, and therefore, it has the potential to increase purchase intention. This research attempts to explain the crucial role of brand awareness in mediating the impact of social media marketing on purchase intention among potential consumers of the online travel agent Traveloka. The study was conducted in the Badung Regency, which is the tourism hub of Bali Province. The sample size consisted of 104 respondents, selected using a non-probability sampling technique from the population of potential Traveloka consumers. The survey was distributed online through the Google Form platform. This research follows a quantitative associative approach, employing path analysis and the Sobel test for analysis. The findings of the study reveal that social media marketing has a positive and significant impact on purchase intention; social media marketing has a positive and significant impact on brand awareness; brand awareness has a positive and significant impact on purchase intention; and brand awareness significantly mediates the effect of social media marketing on purchase intention